1998
DOI: 10.21273/jashs.123.6.1016
|View full text |Cite
|
Sign up to set email alerts
|

Association between DNA Markers and Loci Controlling Avocado Traits

Abstract: The detection of association between DNA markers and traits of interest in an outbred population is complicated and requires highly polymorphic markers. A genetic linkage map of avocado (Persea americana Mill.) recently generated consists of simple sequence repeat (SSR) markers as well as DNA fingerprint (DFP) and randomly amplified polymorphic DNA (RAPD) markers. These markers were used to detect putative quantitative trait loci (QTLs) of eight avocado fruit traits. Two stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…Neither the development nor the maintenance of a mapping population are trivial undertakings for a long-lived organism, but QTL studies have been conducted in many fruit tree genera, including Castanea ( Casasoli et al, 2004 ), Citrus ( Garc í a et al, 2000 ), Coffea ( Amidou et al, 2007 ), Cocos ( Baudouin et al, 2006 ), Malus ( Kenis et al, 2008 ), Prunus ( Quilot et al, 2004 ;Zhang et al, 2010 ), Persea ( Sharon et al, 1998 ), Theobroma ( Crouzillat et al, 1996 ;Crouzillat et al, 2000 ), and Vitis ( Cabezas et al, 2006 ). Because the goal of most of these studies has been crop improvement, crosses have mainly been within the domesticated species (e.g., apple cultivars Telamon × Braeburn; Kenis et al, 2008 ), but also include some wide crosses between two domesticated species (e.g., almond × peach; Illa et al, 2010 ) or between a domesticated species and a wild species that is not a progenitor of the crop [e.g., Citrus limon (L.) Osbeck × Poncirus trifoliata (L.) Raf.…”
Section: Hybridization In Perennial Fruit Crop Lineages -Hybridizatiomentioning
confidence: 99%
See 2 more Smart Citations
“…Neither the development nor the maintenance of a mapping population are trivial undertakings for a long-lived organism, but QTL studies have been conducted in many fruit tree genera, including Castanea ( Casasoli et al, 2004 ), Citrus ( Garc í a et al, 2000 ), Coffea ( Amidou et al, 2007 ), Cocos ( Baudouin et al, 2006 ), Malus ( Kenis et al, 2008 ), Prunus ( Quilot et al, 2004 ;Zhang et al, 2010 ), Persea ( Sharon et al, 1998 ), Theobroma ( Crouzillat et al, 1996 ;Crouzillat et al, 2000 ), and Vitis ( Cabezas et al, 2006 ). Because the goal of most of these studies has been crop improvement, crosses have mainly been within the domesticated species (e.g., apple cultivars Telamon × Braeburn; Kenis et al, 2008 ), but also include some wide crosses between two domesticated species (e.g., almond × peach; Illa et al, 2010 ) or between a domesticated species and a wild species that is not a progenitor of the crop [e.g., Citrus limon (L.) Osbeck × Poncirus trifoliata (L.) Raf.…”
Section: Hybridization In Perennial Fruit Crop Lineages -Hybridizatiomentioning
confidence: 99%
“…Because the goal of most of these studies has been crop improvement, crosses have mainly been within the domesticated species (e.g., apple cultivars Telamon × Braeburn; Kenis et al, 2008 ), but also include some wide crosses between two domesticated species (e.g., almond × peach; Illa et al, 2010 ) or between a domesticated species and a wild species that is not a progenitor of the crop [e.g., Citrus limon (L.) Osbeck × Poncirus trifoliata (L.) Raf. One clear pattern is the instability of the majority of QTLs across years, which requires measurement of the traits of interest across multiple seasons (e.g., Sharon et al, 1998 ;Garc í a et al, 2000 ;Casasoli et al, 2004 ;Quilot et al, 2004 ;Cabezas et al, 2006 ;Kenis et al, 2008 ;Zhang et al, 2010 ). These crosses do not lend themselves easily to answering questions about domestication genetics, but some conclusions can be drawn from them.…”
Section: Hybridization In Perennial Fruit Crop Lineages -Hybridizatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have developed molecular markers for avocado including SNPs from targeted resequencing (Chen et al 2008), and microsatellite markers (Alcaraz and Hormaza 2007;Ashworth et al 2004;Borrone et al 2007;Ge et al 2019;Gross-German and Viruel, 2013;Lavi et al 1994;Mhameed et al 1997;Sharon et al 1997). These markers have been combined with phenotypic data including heritability of nutritional components (Calderon-Vazquez et al 2013) and have been used to identify marker trait associations in avocado (Mhameed et al 1995;Sharon et al 1998). A recent study identified > 250,000 polymorphic SNPs from 22 avocado individuals (Ge et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers in avocado have been used to assess genetic diversity among and within racial groups (Boza et al, 2018;Cuiris-P erez et al, 2009;Gross-German and Viruel, 2013), in phylogenetic studies (Ashworth and Clegg, 2003;Reyes-Alem an et al, 2013), and in construct linkage maps ; to identify quantitative trait loci (Sharon et al, 1998), and in outcrossing studies (Alcaraz and Hormaza, 2011;Borrone et al, 2008;Chen et al, 2007;Garner et al, 2008;Kobayashi et al, 2000;Schnell et al, 2009;Violi et al, 2009). Outcrossing rate studies based on molecular markers have been done in different plant species such as Brassica carinata A. Braun (Teklewold et al, 2013), Foeniculum vulgare Mill.…”
mentioning
confidence: 99%